ESSENTIAL OIL CHARACTERIZATION IN CLOVE (Syzigium aromaticum Linn.) BY GC-MS AND DETECTION OF ITS ADULTERATION BY ATR FTIR METHOD (Applied Biological Research, 2023)
Syzigium aromaticum Linn. (clove) essential oil is known for its dental  analgesic property, and traditionally used as antiseptic, carminative and as  important condiment in foods. Clove essential oil has high medicinal values and its adulteration is done very often with cheap edible oils. The aim of  the present study was to characterize the essential oil constituents and  determine adulteration in essential oils isolated from the buds of clove. The  essential oil composition was determined by GC-MS method and  adulteration by ATR-FTIR method. GC-MS analysis of clove essential oil  yielded 43 chemical compounds with eugenol (59.16%), β-selinene (9.34%),  caryophyllene (7.68%), eugenol acetate (3.35%), and α-humulene (2.16%)  as major compounds. The FTIR of isolated clove essential oil showed a  characteristic peak at 1514 cm-1, which is missing in market essential oil.  The FTIR data of market clove essential oil matches with sesame oil. The  clove essential oil was adulterated with sesame oil (0, 5, 10, 20, 30, 40, 50  and 100% v/v), and the FTIR resultant adulterated binary mixtures  indicated distinct peaks at 2852.72 and 2924.09 cm-1 (for –C-H sp3 & –C-H  sp2 stretching) that is absent in pure essential oil of clove. The present  study provides a simple, economic, quick, reliable, and reproducible  method for detection of adulteration in clove essential oil. GC-MS analysis  further explored the chemical composition of clove essential oil collected  from Erbil, Iraq.
Keywords: Adulteration; ATR-FTIR; clove; GC-MS analysis; Myrtaceae; Syzigium aromaticum